Empowering and engaging industrial workers with Operator 4.0 solutions. (January 2020) - Kaasinen, Eija; Schmalfuß, Franziska; Özturk, Cemalettin; Aromaa, Susanna; Boubekeur, Menouer; Heilala, Juhani; Heikkilä, Päivi; Kuula, Timo; Liinasuo, Marja; Mach, Sebastian; Mehta, Rakesh; Petäjä, Esko; et al.
Highlights: Strong interest towards virtual factory based learning with real-life problem solving tasks. Needs for easily accessible platform for knowledge sharing. Willingness to participate in designing one's own work. Doubts towards worker monitoring, highlighting that solutions need to be designed in close collaboration with workers. Abstract: Industry 4.0 has potential for qualitative enrichment of factory work: a more interesting working environment, greater autonomy and opportunities for self-development. A central element of Industry 4.0 is human-centricity, described as development towards Operator 4.0. Our Operator 4.0 vision includes smart factories of the future that are perfectly suited for workers with different skills, capabilities and preferences. The vision is achieved by solutions that empower the workers and engage the work community. Empowering the worker is based on adapting the factory shop floor to the skills, capabilities and needs of the worker and supporting the worker to understand and to develop his/her competence. Engaging the work community is based on tools, with which the workers can participate in designing their work and training, and share their knowledge with each other. We gathered requirements from three manufacturing companies in different industries and interviewed 44 workers in four factories in order to study their expectations and concerns related to the proposed Operator 4.0 solutions. Adaptation was considered useful both in manufacturing systems and in production planning. However, worker measuring and modelling raised many doubts within workers and also with factory management. Therefore it is important to provide early demonstrations of the ideas and to design them further with the workers in order to find acceptable and ethically sustainable ways for worker modelling. The workers would like to be more involved in the design of the work place and manufacturing processes, and they thought that participation would decrease many problems that they currently face in their work. However, there were also doubts concerning whether they really could have possibilities to impact on their work. The results show that there are clear needs for knowledge sharing and adaptive learning solutions that would support personalized competence development and learning while working. An easily accessible platform for knowledge sharing could evolve to a forum where good work practices and ways to solve problems are shared not only within the work community, but also with machine providers and other stakeholders. The interviewees saw the virtual factory as a promising platform for participatory design and training.